SKIP‐HOPS recruits TBC1D15 for a Rab7‐to‐Arl8b identity switch to control late endosome transport. (21st February 2020) - Jongsma, Marlieke LM; Bakker, Jeroen; Cabukusta, Birol; Liv, Nalan; van Elsland, Daphne; Fermie, Job; Akkermans, Jimmy LL; Kuijl, Coenraad; van der Zanden, Sabina Y; Janssen, Lennert; Hoogzaad, Denise; van der Kant, Rik; et al.
Abstract: The endolysosomal system fulfils a myriad of cellular functions predicated on regulated membrane identity progressions, collectively termed maturation. Mature or "late" endosomes are designated by small membrane‐bound GTPases Rab7 and Arl8b, which can either operate independently or collaborate to form a joint compartment. Whether, and how, Rab7 and Arl8b resolve this hybrid identity compartment to regain functional autonomy is unknown. Here, we report that Arl8b employs its effector SKIP to instigate inactivation and removal of Rab7 from select membranes. We find that SKIP interacts with Rab7 and functions as its negative effector, delivering the cognate GAP, TBC1D15. Recruitment of TBC1D15 to SKIP occurs via the HOPS complex, whose assembly is facilitated by contacts between Rab7 and the KMI motif of SKIP. Consequently, SKIP mediates reinstatement of single identity Arl8b sub‐compartment through an ordered Rab7‐to‐Arl8b handover, and, together with Rab7's positive effector RILP, enforces spatial, temporal and morphological compartmentalization of endolysosomal organelles. Synopsis: GTPases Rab7 and Arl8b reside on late endosomal and lysosomal membranes, and utilize various effector proteins to direct vesicle transport and fusion. The dual‐specificity effector SKIP engages both Rab7 and Arl8b GTPases on late endosomes and facilitates the recruitment of factors responsible for Rab7 inactivation and displacement, to control spatiotemporal compartmentalization of endosomes. SKIP is a negative effector of Rab7. SKIP‐associated HOPS complex binds both Arl8b and Rab7 GTPases. The Arl8b/SKIP/HOPS complex recruits GAP TBC1D15 for inactivating and removing Rab7 from endosomal membranes, giving rise to an Arl8b‐specific compartment. Rab7‐to‐Arl8b GTPase switch mechanism follows the Rab5‐to‐Rab7 conversion paradigm, defining the next step in maturation of endolysosomal organelles. Abstract : SKIP engages both Rab7 and Arl8b GTPases on late endosomes and facilitates the recruitment of factors responsible for Rab7 inactivation and displacement, to control spatiotemporal compartmentalization of endosomes.